How To Identify the Wildlife Species Responsible for Damage in Your Yard - Holly K. Ober; Arlo Kane (EDIS)
Although many homeowners enjoy wildlife in their yards, there are situations where wildlife can become a nuisance. In some circumstances, wild animals can cause extensive damage to lawns and gardens. Learning to identify which species is responsible for this damage is the first step in finding a solution to the problem. This 6-page fact sheet provides images of wildlife damage in residential settings to help you determine which species may be causing similar problems in your yard. Written by Holly K. Ober and Arlo Kane, and published by the UF Department of Wildlife Ecology and Conservation, October 2012.